LASERS : Temporal compression of pulses from a 100-KHz-repetiton-rate femtosecond ytterbium laser. (31st August 2016) - Didenko, N V; Konyashchenko, A V; Kostryukov, P V; Losev, L L; Pazyuk, V S; Tenyakov, S Yu; Bryukhanov, V V
Abstract: We report the temporal compression a femtosecond ytterbium laser pulse at a pulse repetition rate of 100 kHz using the effect of nonlinear self-phase modulation in a gas-filled capillary. A 260-fs laser pulse is compressed down to 17 fs with an energy efficiency of 40%. An average radiation power at the compressor output is 2 W. At a second compression stage, the time contrast is increased and the pulse duration is reduced in the process of the second harmonic generation in a KDP crystal. The obtained pulses have a duration of 11 fs at an efficiency of 35%.